Three-Bar structure optimality criterion using the linear resizing rule - Ramirez Monares, Jose Alfredo (2021)
The static analysis of the indeterminate three-bar structure is developed using the Castigliano’s first theorem, taking the lengths and inclination angles as variables. Some reductions are applied in the resulting set of equations to approximate them to the references models. From now on, the minimum mass optimization model with restrictions is established. Then, the Optimality Criterion linear resizing optimization rule algorithm for the unbounded and bounded design variables is applied in two numerical cases. The analytical and Matlab Optimization Toolbox results are also obtained and they demonstrate the Optimality Criterion linear resizing rule effectiveness in structural optimization with a minimum mass objective and size restrictions.